The Role of Enterprise Architecture in Strategy Work - Kauppila, Eetu (My University, 2023)
Organizational environments are constantly changing and making markets unpredictable. Organizations need to focus on efficiency and effectiveness to achieve their strategic objectives. They may have a good strategy in place, but its implementation and concreteness can pose challenges. Properly exploited, an enterprise architecture can help to improve capabilities and thus respond to changes in the business environment. It enables an organization to assess, plan and monitor strategy work at a concrete level. The aim of the study is to find out what role the architecture plays in strategy work, how it is used and how it could be used. The theoretical background of the study is based on the research literature on architecture and strategy. The theoretical part of the study deals with enterprise architecture, dynamic capabilities, different tools, and frameworks for enterprise architecture. The literature also discusses capabilities, strategy implementation, processes, and strategy tools from a strategy perspective. Due to its nature, the study has been conducted as a qualitative study. Qualitative research is suitable as a research method because it allows the research questions to be approached from a perspective that addresses the interviewees' own experiences and perceptions. Six interviews were conducted, three of the interviewees worked on strategy and three were enterprise architects in different organizations. The data collection was carried out through semi-structured thematic interviews to obtain the most comprehensive information from the interviewees for the study. The interview data collected in the study has been analyzed using qualitative content analysis, as it allows for a systematic and objective analysis of poorly structured documents. The results of the study show that the role of enterprise architecture in strategy work is very limited. The use of enterprise architecture in strategy work varies from company to company, ranging from mere IT department activity to strategy enabling, depending on the organization’s own preferences for using architecture. The term enterprise architecture and its abstract concept are not clear in organizations, which is part of the reason that a holistic change in enterprise architecture requires major changes in organizational cultures, according to the research. The findings suggest that the enterprise architecture is a business and management tool, and its comprehensive approach can help organizations achieve their strategic goals. The enterprise architecture should be involved in the strategy work from the beginning to provide holistic development ideas and assess feasibility.

Organisaatioiden toimintaympäristöt muuttuvat jatkuvasti, joka tekee markkinoista arvaamattomia. Organisaatioiden on keskityttävä tehokkuuteen ja tuloksellisuuteen saavuttaakseen strategiset tavoitteensa. Heillä voi olla laadittuna hyvä strategia mutta sen toimeenpano ja konkretia voivat aiheuttaa haasteita. Oikein hyödynnetty kokonaisarkkitehtuuri voi auttaa parantamaan kyvykkyyksiä ja täten vastaamaan toimintaympäristön muutoksiin. Kokonaisarkkitehtuurin avulla organisaatio pystyy arvioimaan, suunnittelemaan ja seuraamaan strategiatyötä konkreettisella tasolla. Tutkimuksen tavoitteena on selvittää mikä on kokonaisarkkitehtuurin rooli strategiatyössä, miten sitä hyödynnetään ja miten sitä voisi hyödyntää. Tutkimuksen teoreettinen tausta perustuu kokonaisarkkitehtuuria ja strategiaa koskevaan tutkimuskirjallisuuteen. Tutkimuksen teoriaosuudessa käsitellään kokonaisarkkitehtuuria, dynaamisia kyvykkyyksiä, erilaisia kokonaisarkkitehtuurin työkaluja ja viitekehyksiä. Kirjallisuus käsittelee myös strategian näkökulmasta kyvykkyyksiä, strategian toteutumista, prosesseja ja strategiatyökaluja. Tutkimus on toteutettu laadullisena tutkimuksena sen luonteen vuoksi. Laadullinen tutkimus sopii tutkimusmenetelmäksi, koska sen avulla tutkimuskysymyksiä voidaan lähestyä näkökulmasta, joka käsittelee haastateltavien omia kokemuksia ja käsityksiä. Tutkimuksessa toteutettiin kuusi haastattelua, joissa haastateltavista kolme työskenteli strategian parissa ja kolme olivat kokonaisarkkitehtejä eri organisaatioissa. Aineistonkeruu toteutettiin puolistrukturoiduilla teemahaastatteluilla, joissa haastateltavilta saatiin mahdollisimman kattavasti tietoa tutkimukseen. Tutkimuksessa kerätty haastatteluaineisto on analysoitu laadullisen sisällönanalyysin menetelmällä, koska sen avulla voidaan analysoida vähän jäsenneltyjä dokumentteja systemaattisesti ja objektiivisesti. Tutkimustulosten mukaan kokonaisarkkitehtuurin rooli strategiatyössä on hyvin vähäinen. Kokonaisarkkitehtuurin hyödyntäminen strategiatyössä vaihtelee yritysten välillä pelkästä IT- osaston toiminnasta strategian mahdollistamiseen, riippuen organisaation omista preferensseistä käyttää kokonaisarkkitehtuuria. Termi kokonaisarkkitehtuuri ja sen abstrakti konsepti eivät ole selkeitä organisaatioissa, joka on osasyynä, että kokonaisvaltainen muutos arkkitehtuurissa vaatii tutkimuksen perusteella isoja muutoksia organisaatioiden kulttuureissa. Tutkimustulosten mukaan kokonaisarkkitehtuuri on liiketoiminnan ja johdon työkalu ja sen kattava lähestymistapa voi auttaa organisaatioita saavuttamaan strategiset tavoitteensa. Kokonaisarkkitehtuurin tulisi olla mukana strategiatyössä alusta alkaen, jotta se voi tarjota kokonaisvaltaisesti kehitysideoita ja arvioida toteutettavuutta.
Keywords: enterprises; strategies; corporate strategies; strategic leadership; enterprise architecture; strategic planning; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development